STRATEGI PEMBELAJARAN VOKAL ANAK SECARA DARING DI PURWACARAKA MUSIC STUDIO BUARAN - septini, roida; Lucy Martiati (Program Studi Pendidikan Musik, 2022)
At the end of 2019, a new virus was discovered from the city of Wuhan, China. The virus is called coronavirus or commonly known as COVID-19. The closure of educational institutions was something that often happens during the COVID-19 pandemic which aims to avoid the spread of the virus in many countries including Indonesia. Purwacaraka Music Studio (PCMS) Buaran is one of non-formal course institution that changed learning method from in-person learning to online learning, because of the pandemic. The purpose of this study is to perceive the online learning strategy for children aged 7-11 years in vocal class during the COVID-19 pandemic at Purwacaraka Music Studio Buaran. This research used descriptive qualitative method, by using data collection techniques through observation, interviews, and documentation. The outcome of the research states there is a development of children's abilities and interests in vocal learning, this development is caused by new teaching strategy that have been implemented by teachers. The strategy is the lecture method with a brief explanation of the song material that has been adjusted carefully to the abilities of each student. As well as a demonstration method where students are given various vocalizing accompaniments and song material made and recorded by the teacher. This research shows that quality teacher preparation gives an positive impact on learning outcomes in online classes.